Autologous Matrix-Induced Chondrogenesis (AMIC) and Microfractures for Focal Chondral Defects of the Knee: A Medium-Term Comparative Study - Filippo Migliorini; Jörg Eschweiler; Nicola Maffulli; Hanno Schenker; Alice Baroncini; Markus Tingart; Björn Rath (Life, 2021)
Introduction: The potential of autologous matrix-induced chondrogenesis (AMIC) to restore unipolar focal chondral defects of the knee is promising. However, the outcome compared to microfracturing (MFx) for certain defect sizes (2–3 cm2) is still uncertain. Therefore, the present study compared primary isolated AMIC versus MFx in a cohort of patients with borderline sized focal unipolar chondral defects of the knee at midterm follow-up. Methods: Patients with chondral defects of the knee who underwent AMIC or MFx were compared. An arthroscopic approach was used for MFx, and a minimally invasive parapatellar arthrotomy for AMIC. For those patients who underwent AMIC, a collagen membrane was used with fibrin glue. The patients answered independently: Visual Analogic Scale (VAS), Tegner Activity Scale, International Knee Documentation Committee (IKDC), and the Lysholm scores. Results: A total of 83 patients with a mean age of 30.2 and body mass index (BMI) of 26.9 kg/m2 were recruited. Of them, 33.7% (28 of 83) were women, and 55.4% (46 of 83 patients) had defects in the right knee. The mean length of symptoms before surgery was 43.3 months. The mean size of the defect was 2.7 cm2. The mean length of follow-up was 42.1 months. No difference was found in terms of symptoms and follow-up length, mean age and BMI, mean size of defect, sex, and side. The AMIC cohort reported greater IKCD (p > 0.0001), Lysholm (p = 0.002), VAS (p = 0.01), Tegner (p = 0.004) scores. The AMIC cohort reported lower rate of failure (p = 0.005) and revision surgery (p = 0.02). No difference was found in the rate of arthroplasty (p = 0.2). No delamination or hypertrophy were detected. Conclusion: AMIC demonstrated superiority over MFx for focal unipolar chondral defects of the knee. At approximately 40 months follow-up, the IKDC, Lysholm, and VAS scores were greater in the AMIC group. Patients treated with AMIC also demonstrated a higher level of sport activity, and lower rates of failure and revision surgeries.